CUSTOMS AND EXCISE OFFICERS AUTHORITY ON ILLEGAL CIGARETTE IN INDONESIA - Abdul Hamid; Samuel Samuel (Kanun Jurnal Ilmu Hukum, 2022)
Tobacco excise is the largest contributor to revenue in the state budget collected by the Directorate General of Customs and Excise (DGCE). On the other hand, the largest prosecution carried out by DGCE from the top 10 (ten) prosecutions is the prosecution of tobacco products (cigarettes), the success of these prosecutions is inseparable from the administrative authority specifically granted by the Law to the DGCE. This study aims to find out wheter the DGCE authotiy has been exercised with the correct authority. In this study, researchers used doctrinal legal research with qualitative method with primary data. The research shows that law enforcement carried out by customs and excise officials is the administrative authority and this authority is not unlimited. It is appropriate for policy makers to harmonize the procedures for prosecution with limits of authority owned and to provide in-depth understanding thus customs and excise officials.